Modulatory Effects of Antibody Replacement Therapy to Innate and Adaptive Immune Cells - Quinti, Isabella; Mitrevski, Milica (Frontiers in Immunology, 2017)
Intravenous immunogobulin administered at replacement dosages modulates innate and adaptive immune cells in PAD in a different manner to what observed when high dosages are used or when their effect is analyzed by in vitro experimental conditions. The effects seem to be beneficial on innate cells in that dendritic cells maturate, pro-inflammatory monocytes decrease and neutrophil function is preserved. The effects are less clear on adaptive immune cells. IVIg induced a transient increase of Treg and a long-term increase of CD4 cells. More complex and less understood is the interplay of IVIg with defective B cells of PAD patients. The paucity of data underlies the need of more studies on patients with PAD before drawing conclusions on the in vivo mechanisms of action of IVIg based on in vitro investigations